Optimization of Aceclofenac Proniosomes by Using Different Carriers, Part 1: Development and Characterization - Sammour, Rana M.F; Taher, Muhammad; Mahmood, Syed (MDPI, 2019)
In the contemporary medical model world, the proniosomal system has been serving as a new drug delivery system that is considered to significantly enhance the bioavailability of drugs with low water solubility. The application of this system can improve the bioavailability of aceclofenac that is used for the relief of pain and inflammation in osteoarthritis, rheumatoid arthritis, and ankylosing spondylitis. The present study is intended to develop an optimized proniosomal aceclofenac formula by the use of different carriers. Aceclofenac proniosomes have been prepared by slurry method, and different carriers such as maltodextrin, mannitol, and glucose were tried. Prepared proniosomes characterized by differential scanning calorimetry (DSC) analysis and Fourier transform infrared (FTIR) analysis revealed the compatibility of the drug chosen with the ingredient added, powder X-ray diffractometry (XRD) confirmed the amorphous phase of the prepared proniosomes, and finally, the surfactant layer was observed by scanning electron microscopy (SEM). Aceclofenac physical state transformations were confirmed with all formulas but maltodextrin proniosomes exhibited solubility more than other formulations. HPLC method has been used to analyze the niosomes derived from proniosomes in terms of their entrapment capability and drug content. The obtained results revealed that aceclofenac proniosomes can be successfully prepared by using different carriers.